The Development of Traditional Medicine into Modern Medicine: A Review of Its Potential and Challenges - Indrayadi, Indrayadi; Betan, Abu Bakar (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Traditional medicine has been an integral part of public health systems for centuries. With the advancement of science and technology, traditional medicine has begun to be adapted to modern medical approaches through standardization, scientific research, and regulation. This study aims to examine the potential and challenges in transforming traditional medicine into modern medicine. The method used was a literature review, reviewing relevant national and international journals. The results indicate that traditional medicine has great potential as a source of new drugs, increasing accessibility, and providing a wider range of therapeutic options. However, challenges include limited scientific research, a lack of quality standardization, safety and side effect issues, and regulatory constraints. In conclusion, traditional medicine has great potential to be developed into modern medicine, but requires more comprehensive research support, standardization, and adaptive health policies.